IMPLEMENTASI SISTEM MONITORING SUHU DAN KELEMBABAN RUANG PRODUKSI OBAT BERBASIS IoT DENGAN MENGGUNAKAN NodeMCU ESP32 - Muhammad Ilman Mahmudi; Arif Faizin (JOURNAL SAINS STUDENT RESEARCH, 2025)
The drug manufacturing process in the pharmaceutical industry must comply with Good Manufacturing Practices (GMP) standards, including temperature and humidity control to prevent product quality degradation. This study designed an Internet of Things (IoT)-based temperature and humidity monitoring system using NodeMCU ESP32, NTC MF52-103 (temperature) and DHT11 (humidity) sensors. The system is equipped with an alarm if parameters exceed standard limits and can be accessed remotely via an Android application based on MIT App Inventor. Test results show that the system is capable of reading, displaying, storing, and providing real-time notifications of production environment conditions. This implementation is expected to support more effective quality control of pharmaceutical production rooms.